2019
DOI: 10.1007/s11340-019-00477-4
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Field in Diametrically Loaded Soft Cylinders

Abstract: Deformation fields at the surface of diametrically squeezed shallow cylinders in the large deformation regime are measured experimentally and numerically for different material behaviour in the large deformation regime. By means of a digital image correlation method optimized for large displacements, strain fields are measured and compared with finite element simulations. Assuming a neo-Hookean behaviour for cylinders made of rubber silicone, the strain field is found to be in quantitative agreement with non-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…As shown in fig. 10a and b, in agreement with what is observed for a single particle [50] (see the inset of fig.6a) , C is homogeneously equals to 1 at the beginning of the compression and then rapidly decreases both in the center and very close to the edges of the particles. On the contrary, in between, few millimeters away from the edges, the von Mises strain increases and can even reach values higher than 1 in this area where the shear strain is dominant.…”
Section: Strain Field Evolutionsupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in fig. 10a and b, in agreement with what is observed for a single particle [50] (see the inset of fig.6a) , C is homogeneously equals to 1 at the beginning of the compression and then rapidly decreases both in the center and very close to the edges of the particles. On the contrary, in between, few millimeters away from the edges, the von Mises strain increases and can even reach values higher than 1 in this area where the shear strain is dominant.…”
Section: Strain Field Evolutionsupporting
confidence: 89%
“…Set-up One of the most challenging point when dealing with experimental study of highly strained granular matter is to make quantitative measurements at the grain scale for the whole packing. To overcome this challenge, we used the novel set-up already presented in Vu et al [50] and shown in fig. 1a.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Uniaxial compressions of bidisperse assemblies of elastic rubberlike particles were carried out with the experimental setup introduced in the previous works [13,14] for studying the compression of a single particle. It consists of a compression device placed on a horizontal flatbed scanner as shown in Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These surfaces are coated with a shiny thin glitter layer (glitter mean size of 20 μm), consisting of a random and homogeneous pattern on the bottom of the particles with a high black-and-white contrast. This pattern is used to get the displacement field of each particle by means of a digital image correlation (DIC) algorithm introduced in previous works [13,14] in which the deformations of a unique particle were investigated. In order to apply this algorithm to the case of an assembly of particles, the positions of the particles are first tracked step by step, and the rigid body motion of each particle is determined and withdrawn before the application of the DIC algorithm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation